reproducible assay for measuring partial resistance to Sclerotinia sclerotiorum in soybean - Bastien, Maxime; Tung Thanh Huynh; GeneviÃ¨ve Giroux; Elmer Iquira; Sylvie Rioux; FranÃ§ois Belzile (Canadian journal of plant science, 2012)
Bastien, M., Huynh, T. T., Giroux, G., Iquira, E., Rioux, S. and Belzile, F. 2012. A reproducible assay for measuring partial resistance toSclerotinia sclerotiorumin soybean. Can. J. Plant Sci. 92: 279â288. In eastern Canada, Sclerotinia stem rot in soybean is an important disease, and resistance is systematically assessed in cultivar performance trials. The reference method used in these trials closely mimics the natural infection process, but is very demanding, and its success is highly subject to environmental conditions. Here we describe a simple, quick and reproducible inoculation method to measure resistance to pathogen progression on the main stem. Importantly, this method is the first to reproducibly identify quantitative trait loci (QTLs) conferring partial resistance to Sclerotinia stem rot in soybean. In this method, a cotton pad saturated with a mycelial suspension is applied to a floral bud and resistance is estimated by measuring lesion length on the main stem. The method was found to discriminate clearly between known resistant and susceptible checks in both the field and greenhouse. Clear discrimination between 26 recombinant inbred lines (RILs) contrasted for QTLs controlling resistance to Sclerotinia stem rot was also achieved in four independent trials, and lesion length was significantly correlated among all trials. When tested on 38, 42 and 40 lines in registration trials, the results of this method were significantly correlated with those of the reference method in 2 of 3 yr.